Biomass derived material-based oxygen electrocatalyst and preparation method thereof

By generating Co2P nanoparticles in situ on biomass-derived materials and forming a heterojunction interface with MnO2 clusters, forming hollow spherical nanoparticles with multiple facets, solving the problems of high cost and insufficient stability of traditional catalysts, and achieving efficient catalytic activity of oxygen reduction reactions, ultra-high stability and methanol resistance.

CN119833653AActive Publication Date: 2025-04-15NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411768971.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-15
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing metal-based catalysts such as Pt/C have problems such as high cost, limited methanol tolerance and insufficient stability in large-scale applications, making it difficult to meet the needs of sustainable development.

Method used

Using an oxygen electrocatalyst based on biomass-derived materials, Co2P nanoparticles are generated in situ by P and metal Co in the phospholipid bilayer, and synergistically enhance the heterojunction interface composed of MnO2 clusters to form hollow spherical nanoparticles with multiple facets.

Benefits of technology

It achieves efficient catalytic activity of oxygen reduction reaction (ORR), with ultra-high stability and methanol resistance, and overcomes the cost and stability problems of traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833653A_ABST
    Figure CN119833653A_ABST
Patent Text Reader

Abstract

The invention provides an oxygen electrocatalyst based on a biomass derived material and a preparation method of the oxygen electrocatalyst. The preparation method specifically comprises the following steps: S1, preparing a staphylococcus aureus sample containing Co; s2, dispersing the staphylococcus aureus sample prepared in the step S1 as a biomass template in a methanol solution containing Co < 2 + >, Zn < 2 + > and Mn < 2 + > to obtain a solution A; s3, dissolving 2-methylimidazole in methanol to obtain a solution B; s4, mixing the solution A and the solution B, and performing stirring reaction and centrifugation to obtain a semi-finished product; and S5, performing pyrolytic reaction on the semi-finished product obtained in the step S4 to obtain the oxygen electrocatalyst. Compared with the prior art, the preparation method has the advantages that the advantages of a biomass material are combined, staphylococcus aureus is selected as a biomass template, the microstructure and intrinsic catalytic activity sites of the biomass template are constructed in a self-assembly mode, and the hollow spherical self-supporting oxygen electrocatalyst (MnO2 / Co2P (at) SDHC) of composite nanoparticles loaded with MnO2 / Co2P heterostructure on the near-micron scale is prepared; the catalyst realizes excellent catalytic performance and has ultrahigh stability and methanol resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to an oxygen electrocatalyst based on biomass-derived materials and a preparation method thereof. Background Art

[0002] Metal-based catalysts, such as Pt / C, are widely used as standard catalysts due to their excellent ORR catalytic activity and can effectively enhance the cathode reaction kinetics.

[0003] However, the large-scale application and sustainability of Pt / C are restricted by its high cost, limited methanol tolerance and insufficient stability. Biomass materials are natural precursor materials for a class of green and renewable carbon-based catalysts, which are widely distributed in nature, have orderly structures and are rich in heteroatoms, but their large size and rigid structure themselves limit the full utilization of their microstructural advantages. In contrast, microorganisms, such as bacteria with near-micrometer-specific macrostructures, are perfect biomass templates for oxygen electrocatalysts. By modifying them, efficient intrinsic catalytic activity can be obtained while inheriting the biomass structure. Summary of the invention

[0004] In order to solve the above-mentioned technical problems, the present invention provides an oxygen electrocatalyst based on biomass-derived materials and a preparation method thereof to overcome the shortcomings of the prior art.

[0005] The present invention provides an oxygen electrocatalyst based on biomass-derived materials. The oxygen electrocatalyst is Co2P hollow spherical nanoparticles, contains a heterojunction interface composed of MnO2 clusters, has a multi-faceted undulating rough surface, and has a diameter of 1±0.2um.

[0006] Compared with the existing technology, P and metal Co in the phospholipid bilayer are in situ generated Co2P nanoparticles with high ORR activity, and the heterojunction interface composed of MnO2 clusters synergistically enhances the intrinsic reaction kinetics; the irregular hollow spherical structure can construct a microenvironment near the electrode that is conducive to ORR mass transfer efficiency. The catalyst has a clear structure and has ultra-high stability and methanol resistance.

[0007] The second object of the present invention is to provide a method for preparing an oxygen electrocatalyst, the preparation method specifically comprising the following steps:

[0008] S1. preparing a Staphylococcus aureus sample containing Co;

[0009] S2, dispersing the Staphylococcus aureus sample prepared in step S1 as a biomass template in a 2+ 、Zn 2+ and Mn 2+ Solution A is obtained from a methanol solution;

[0010] S3, dissolving 2-methylimidazole in methanol to obtain solution B;

[0011] S4, mixing solution A and solution B, stirring, reacting and centrifuging to obtain a semi-finished product;

[0012] S5. The semi-finished product obtained in step S4 is subjected to a pyrolysis reaction to obtain an oxygen electrocatalyst.

[0013] Compared with the prior art, the present invention combines the advantages of biomass materials, selects Staphylococcus aureus (S. aureus) as a biomass template, constructs its microstructure and intrinsic catalytic active sites in a self-assembly manner, and prepares a hollow spherical self-supporting oxygen electrocatalyst (MnO2 / Co2P@SDHC) loaded with composite nanoparticles of MnO2 / Co2P heterostructure on a near-micrometer scale, which achieves excellent catalytic performance and has ultra-high stability and methanol resistance.

[0014] In a possible implementation manner, the steps of step S1 are as follows:

[0015] S11, culturing Staphylococcus aureus as a biomass material in a culture medium, and collecting bacterial cells by centrifugation after the cultivation is completed;

[0016] S12. The bacterial cells are mixed in a mixed solvent, a cobalt nitrate solution is added for stirring, and then centrifugation, washing and freeze-drying are performed in sequence to obtain a Staphylococcus aureus sample containing Co.

[0017] Compared with the prior art, the present invention adopts the above technology, wherein the cell wall and internal structure of Staphylococcus aureus can provide a natural three-dimensional template, which is helpful to form a catalyst with a specific morphology and structure. By mixing and stirring the bacterial cells with the cobalt nitrate solution, the Co 2+ The ions are evenly adsorbed on the surface or inside of the bacterial cells, which helps to ensure the uniform distribution of the metal components in the subsequently generated catalyst. By loading the metal ions on the bacterial cells, more active sites can be formed after pyrolysis, thereby improving the electrocatalytic activity of the catalyst.

[0018] In a possible embodiment, in step S11, the culture medium is Luria Broth culture medium, the culture method is shaking culture, and the parameters are as follows: temperature is 30° C., speed is 180 rpm, and time is 18 h.

[0019] Compared with the prior art, the present invention adopts the above parameters for cultivation, and its advantages are: LB (Luria Broth) medium is a commonly used bacterial culture medium, rich in protein, carbon source and other essential nutrients, and can support the rapid growth of Staphylococcus aureus. The 18-hour culture time is enough for the bacteria to reach a higher cell density, while avoiding resource exhaustion or accumulation of metabolites caused by excessive growth. Through oscillation culture (180rpm), it can ensure that the nutrients and oxygen in the culture medium are evenly distributed, and promote the consistent growth of bacteria throughout the culture process, which helps to obtain a more uniform biological template; 30°C is one of the ideal temperature ranges for the growth of Staphylococcus aureus. This temperature will not be too high to cause heat stress, nor will it be too low to affect the growth rate, which helps to maintain the optimal physiological state of bacteria. Using LB medium for 18 hours at 30°C and oscillating at a speed of 180rpm can effectively promote the growth of Staphylococcus aureus and provide a high-quality biomass template, thereby laying a good foundation for subsequent metal ion adsorption and catalyst preparation.

[0020] In a possible implementation, in step S11, the specific step of centrifugation is: collecting bacterial cells by centrifugation at 5000 rpm for 5 min at 4° C., and then washing with sterile deionized water for 3 times.

[0021] Compared with the prior art, the advantages of the centrifugation step in the present invention are: 5000 rpm is a relatively high centrifugation speed, which can effectively separate the bacterial cells from the culture medium, ensuring that the precipitate is mainly bacterial cells, while the nutrients and other impurities in the supernatant are removed; 5 minutes is sufficient to complete effective cell precipitation, while avoiding the mechanical damage to the cells that may be caused by long-term centrifugation; centrifugation at 4°C helps to maintain the activity and structural integrity of the bacterial cells, and low temperature can reduce the activity of enzymes and prevent the degradation of intracellular components, thereby maintaining the cells in the best state.

[0022] In a possible embodiment, the specific steps of step S12 are as follows: dispersing Staphylococcus aureus powder in a mixed solvent of ethanol and sterile deionized water, ultrasonically treating for 30 minutes, adding 0.1M cobalt nitrate solution under stirring, and continuing stirring for 12 hours, centrifuging and washing, and then freeze-drying for 12 hours to obtain a Co-containing Staphylococcus aureus sample.

[0023] Compared with the prior art, the present invention adopts the above-mentioned treatment method to obtain a Co-containing Staphylococcus aureus sample, and its effects are: using a mixed solvent of ethanol and sterile deionized water can provide a good dispersion medium, which is conducive to the uniform distribution of bacterial cells in the solution; 30 minutes of ultrasonic treatment can further break up cell agglomerations, ensure that each cell can fully contact the solvent, and improve the uniformity of subsequent metal ion adsorption; adding 0.1M cobalt nitrate solution under stirring and continuing to stir for 12 hours can ensure that the metal ions have enough time to fully contact and adsorb with the surface or inside of the bacterial cells to form a stable complex; 0.1M cobalt nitrate solution provides an appropriate metal ion concentration, which will neither cause precipitation due to excessively high concentration nor affect the adsorption effect due to too low concentration.

[0024] In a possible implementation manner, the volume ratio of the ethanol to the sterile deionized water is 2:1.

[0025] Compared with the prior art, the present invention limits the volumes of ethanol and sterile deionized water within the above range. Ethanol is an organic solvent with certain polarity and solubility, while sterile deionized water is a polar solvent. A mixed solvent with a volume ratio of 2:1 can provide an environment with both good polarity and certain non-polarity, which is conducive to the uniform dispersion of bacterial cells in the solution; the presence of ethanol can increase the permeability of the solvent to the cell wall, which helps the cobalt nitrate solution to better enter the interior of the cell, thereby improving the adsorption efficiency of metal ions.

[0026] In a possible implementation, in step S2, the specific preparation process of solution A is as follows: Staphylococcus aureus containing Co obtained in step S1, cobalt nitrate, zinc nitrate, manganese acetate and methanol are mixed, and the mixture is ultrasonically treated for 0.5 h and then stirred for 1 h to obtain the solution.

[0027] Compared with the existing technology, by adding cobalt nitrate, zinc nitrate and manganese acetate at the same time, a multi-metal-doped precursor can be formed on the bacterial template, which helps to improve the electrochemical performance of the final catalyst; the synergistic effect between different metal elements can optimize the electron transfer process and improve the activity of the catalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER).

[0028] In a possible implementation, in step S4, the stirring reaction parameters are as follows: the temperature is room temperature, and the time is 5 hours.

[0029] In a possible implementation, in step S5, the specific steps of the pyrolysis reaction are: pyrolysis at a rate of 5°C / min in an argon atmosphere, first heating to 250°C and maintaining for 60 minutes, then heating to 950°C and maintaining for 120 minutes.

[0030] Compared with the prior art, the present invention adopts the above parameters for pyrolysis reaction, and its role is: pyrolysis in an argon atmosphere can effectively prevent the material from being oxidized at high temperature, ensure the purity of the generated carbon-based material and metal nanoparticles, and heat at a slow heating rate of 5°C / min, which can reduce the thermal stress caused by the sudden temperature change and avoid cracks or structural damage inside the material. Keeping at 250°C for 60 minutes can effectively remove moisture, organic solvent residues and other volatile substances in the sample, creating good conditions for subsequent high-temperature pyrolysis, and keeping at 950°C for 120 minutes can ensure that the bacterial cell template is completely carbonized to form a stable carbon-based material. Using this specific pyrolysis step, the temperature can be gradually increased in an inert atmosphere, and the full carbonization of the material and the uniform distribution of the metal nanoparticles can be ensured by processing at different temperature sections, thereby preparing a high-performance oxygen electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of the MnO2 / Co2P@SDHC catalyst prepared in Example 1;

[0032] Figure 2 LSV diagram of ORR test of MnO2 / Co2P@SDHC catalyst. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0034] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0035] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0036] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0037] Example 1

[0038] This embodiment provides an oxygen electrocatalyst based on biomass-derived materials, which is prepared by the following preparation method:

[0039] Staphylococcus aureus was cultured in LB (Luria Broth) medium at 30°C and 180 rpm. After culturing for 18 hours, the bacterial cells were collected by centrifugation at 5000 rpm for 5 minutes at 4°C, and then washed three times with sterile deionized water. About 0.3 g of Staphylococcus aureus powder was dispersed in a mixture of 60 ml of ethanol and sterile deionized water (ethanol: sterile deionized water = 2:1, v / v), and after ultrasonic treatment for 30 minutes, 10 ml of 0.1 M cobalt nitrate solution was added under stirring, and stirring was continued for 12 hours. The Co-containing Staphylococcus aureus sample was obtained by centrifugation and washing several times, and then freeze-dried for 12 hours;

[0040] 50 mg of the prepared Co-containing Staphylococcus aureus, 0.0989 g of cobalt nitrate, 0.1 g of zinc nitrate, and 0.05 g of manganese acetate were dispersed in 20 mL of methanol, and the mixture was ultrasonicated for 0.5 h and then stirred for 1 h to form solution A.

[0041] 1.845 g of 2-Melm was dissolved in 45 mL of methanol to form a solution;

[0042] Solution A and solution B were mixed, stirred at low speed for 5 h at room temperature, and centrifuged to obtain the sample CoZnMn-ZIF67@S.aureus, which was washed several times and dried in a vacuum oven overnight;

[0043] The sample CoZnMn-ZIF67@S.aureus was pyrolyzed in an argon atmosphere at a rate of 5 °C / min, first kept at 250 °C for 60 min to maintain its spherical structure, and then heated to 950 °C and kept for 120 min to obtain the sample MnO2 / Co2P@SDHC.

[0044] The oxygen electrocatalyst prepared in this embodiment was observed, and its scanning electron microscope image is as follows: Figure 1 As shown, from Figure 1 It can be seen that the golden grape has a multi-faceted undulating rough surface with a diameter of about 1 μm.

[0045] Example 2

[0046] 5 mg of the oxygen electrocatalyst prepared in Example 1, 500 μL of ethanol and 30 μL of Nafion solution were ultrasonically mixed to form a uniform catalyst ink, and 10 μL of the oxygen electrocatalyst ink was evenly dropped on the surface of the rotating disk ring electrode and dried naturally at room temperature. ORR test was carried out in 0.1 M KOH saturated with oxygen using Ag / AgCl as the reference electrode and carbon rod as the counter electrode. The obtained LSV diagram is shown in FIG. Figure 2 As shown, the half-wave potential is 0.83V and the starting potential is 0.95V.

[0047] From the above results, it can be seen that the present invention combines the advantages of biomass materials, selects Staphylococcus aureus (S. aureus) as a biomass template, constructs its microstructure and intrinsic catalytic active sites in a self-assembly manner, and prepares a hollow spherical self-supporting oxygen electrocatalyst (MnO2 / Co2P@SDHC) loaded with composite nanoparticles of MnO2 / Co2P heterostructure on a near-micrometer scale, which achieves excellent catalytic performance and has ultra-high stability and methanol resistance.

[0048] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. An oxygen electrocatalyst based on biomass-derived materials, characterized in that The oxygen electrocatalyst is Co2P hollow spherical nanoparticles, contains a heterojunction interface composed of MnO2 clusters, has a multi-faceted undulating rough surface, and has a diameter of 1±0.2um.

2. The method for preparing an oxygen electrocatalyst according to claim 1, characterized in that: The preparation method specifically comprises the following steps: S1. preparing a Staphylococcus aureus sample containing Co; S2, dispersing the Staphylococcus aureus sample prepared in step S1 as a biomass template in a 2+ 、Zn 2+ and Mn 2+ Solution A is obtained from a methanol solution; S3, dissolving 2-methylimidazole in methanol to obtain solution B; S4, mixing solution A and solution B, stirring, reacting and centrifuging to obtain a semi-finished product; S5. The semi-finished product obtained in step S4 is subjected to a pyrolysis reaction to obtain an oxygen electrocatalyst.

3. The preparation method according to claim 2, characterized in that: The steps of step S1 are as follows: S11, culturing Staphylococcus aureus as a biomass material in a culture medium, and collecting bacterial cells by centrifugation after the cultivation is completed; S12. The bacterial cells are mixed in a mixed solvent, a cobalt nitrate solution is added for stirring, and then centrifugation, washing and freeze-drying are performed in sequence to obtain a Staphylococcus aureus sample containing Co.

4. The preparation method according to claim 3, characterized in that: In step S11, the culture medium is Luria Broth culture medium, the culture method is shaking culture, and the parameters are as follows: temperature is 30° C., speed is 180 rpm, and time is 18 h.

5. The preparation method according to claim 3, characterized in that: In step S11, the specific steps of centrifugation are: collecting bacterial cells by centrifugation at 5000 rpm for 5 min at 4°C, and then washing with sterile deionized water for 3 times.

6. The preparation method according to claim 3, characterized in that: The specific steps of step S12 are as follows: dispersing Staphylococcus aureus powder in a mixed solvent of ethanol and sterile deionized water, ultrasonically treating for 30 minutes, adding 0.1M cobalt nitrate solution under stirring, and continuing stirring for 12 hours, centrifuging and washing, and then freeze-drying for 12 hours to obtain a Co-containing Staphylococcus aureus sample.

7. The preparation method according to claim 6, characterized in that: The volume ratio of the ethanol to the sterile deionized water is 2:

1.

8. The preparation method according to claim 2, characterized in that: In step S2, the specific preparation process of solution A is as follows: Staphylococcus aureus containing Co obtained in step S1, cobalt nitrate, zinc nitrate, manganese acetate and methanol are mixed, and the mixture is ultrasonically treated for 0.5 h and then stirred for 1 h to obtain the solution.

9. The preparation method according to claim 2, characterized in that: In step S4, the stirring reaction parameters are as follows: the temperature is room temperature, and the time is 5 hours.

10. The preparation method according to claim 2, characterized in that: In step S5, the specific steps of the pyrolysis reaction are: pyrolysis at a rate of 5°C / min in an argon atmosphere, first heating to 250°C and maintaining for 60 minutes, then heating to 950°C and maintaining for 120 minutes.

Citation Information

Patent Citations

  • Water electrolytic hydrogen production catalytic electrode of self-supporting metal-doped cobalt phosphide nano structure

    CN105839131A

  • Method for preparing tricobalt tetraoxide nanosheet by double confinements of MOF-Co and biological template

    CN110357172A

  • Catalyst structure for ozone decomposition

    CN111050905A

  • N,P-doped carbon fiber loaded FeCo / Co2P composite catalyst and preparation method thereof

    CN111151279A

  • Metal organic framework material, application thereof and aptamer sensor

    CN114276558A